Optimizing Business Processes through Information System Integration A Case Study in Banda Aceh - Sarno; Maulidar (Journal Informatic, Education and Management (JIEM), 2024)
This research aims to optimize business processes through information system integration using a case study in Banda Aceh. This research uses a qualitative approach with a single case study research method. Data was collected through in-depth interviews, direct observation and documentation. Research respondents consist of managers and employees involved in the business processes to be integrated. Data analysis was carried out using content analysis. The research results show that information system integration significantly increases the efficiency and effectiveness of business processes in Banda Aceh. Information system integration enables faster data processing, better monitoring of business processes, and more accurate decision making. Additionally, information system integration also enables better collaboration between different departments and stakeholders. Based on these findings, it can be concluded that information system integration plays an important role in optimizing business processes in Banda Aceh. By integrating information systems, companies can increase operational efficiency, reduce costs, and increase customer satisfaction. However, the implementation of information systems integration also faces challenges, such as technical difficulties and changes in organizational culture. Therefore, strong commitment and support from company management is needed to achieve optimal results.